A Rapid Method to Quantify Fungicide Sensitivity in the Brown Rot Pathogen Monilinia fructicola - Cox, Kerik D (Plant disease, 2009)
Management of brown rot of stone fruit relies upon the application of effective fungicides that may be compromised by the development of fungicide resistance. We evaluated fungicide resistance in the brown rot pathogen, Monilinia fructicola, using Alamar blue (AB) dye, or resazurin, a chromogenic substrate that can be used as an indicator of respiration, in a 96-well microtiter format. We compared the AB method to traditional mycelial growth assays for resistance screening using 10 isolates of M. fructicola that represented a range of sensitivities to fenbuconazole. Using traditional mycelial growth assays, isolate sensitivity ranged from 17.7 to 115.3% growth on medium amended with fenbuconazole at 0.03 μg/ml relative to that on nonamended medium. Concordant results between both assays were obtained (R2 = 0.9943, P < 0.0001), but the AB method provided results within 24 h, as opposed to the 3- to 5-day period required for mycelial growth assays. We found that sensitive isolates reduced AB less than resistant isolates in the presence of fungicide. Spore density influenced the reduction of AB by M. fructicola; spectrophotometric discrimination of fungicide sensitivity was best achieved at a density of 105 spores/ml